(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Burn injuries are under-appreciated injuries that are associated with substantial morbidity and mortality. Burn wound healing is a complicated process that includes inflammation, re-epithelialization, granulation, neovascularization, and wound contraction. Initial treatment of burn wounds aims at preventing infection and early wound healing. Properties like antioxidant, anti-inflammatory, antimicrobial, antibacterial are also helps in wound healing. The level of severity of the burn is of the utmost importance. Third degree burns require immediate medical attention while studies suggest that a number of natural remedies may aid in the treatment of first- and second-degree burns. The basic concepts and principles of management of burn injury is described in Ayurveda are very much relevant and useful in this era of modern surgery. There are so many herbs mentioned in Ayurveda classics are found to have properties like Dagdhahara, Vrana prasamana, Pittahara, Varnaprasadana, Twacya etc which contributes to burn wound healing. More recently, scientists increasingly rely on modern scientific methods and evidence based medicine to prove efficacy of herbal medicine and focus on better understanding of mechanisms of their action. The purpose of this article is to review the evidence supporting the use of some of the Ayurvedic herbal drugs and formulations as effective and affordable treatments for burn wounds.